Rail (real) safety issues: predictive maintenance for Singapore railway - Khoo, Alyna Yi Jie (Nanyang Technological University, 2022)
This Final Year Project (FYP) aims to evaluate the possibility of performing fault prediction in Singapore’s rail network from available data. The quest to predict railway faults in Singapore is still underway, spearheaded by the Rail Enterprise Asset Management System (REAMS) project jointly led by SIEMENS and ST Engineering Consortium formed in 2018.